Progress in Pattern Recognition, Image Analysis, Computer Vision, and Applications 15th Iberoamerican Congress on Pattern Recognition, CIARP 2010, Sao Paulo, Brazil, November 8-11, 2010. Proceedings - Bloch, Isabelle; Cesar, Roberto M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 15th iberoamerican Congress on Pattern Recognition, CIARP 2010, held in Sao Paulo, Brazil, in November 2010. The 70 revised full papers presented were carefully reviewed and selected from 145 submissions. The papers feature current research on mathematical methods and computing techniques for pattern recognition, computer vision, image analysis, and speech recognition, as well as their applications in such diverse areas as robotics, industry, health, entertainment, space exploration, telecommunications, data mining, document analysis, and natural language processing and recognition to name only few of them.
Invited Talks -- Color, Shape and Texture -- Graphs and Hypergraphs -- Biomedical Imaging -- Retrieval, Mining and Learning -- Learning, Recognition and Clustering -- Bayesian and Statistical Methods -- Coding and Compression, Video, Tracking -- Speech, Natural Language, Document -- Image Filtering and Segmentation -- Feature Extraction, Shape, Texture, Geometry and Morphology -- Face Segmentation and Recognition, Biometry -- Statistical Approaches, Learning, Classification, Mining.
Keywords: Computer science; Computer software; Artificial intelligence; Computer vision; Optical pattern recognition; Biometrics; Computer Science; Pattern Recognition; Image Processing and Computer Vision; Artificial Intelligence (incl. Robotics).; Computer Imaging, Vision, Pattern Recognition and Graphics; Biometrics; Algorithm Analysis and Problem Complexity